Potential health gains in West and Central Africa through savings from lower cost HIV treatment. (1st March 2020) - Stuart, Robyn M.; Kelly, Sherrie L.; Martin-Hughes, Rowan; Wilson, David P.
Abstract : Objective: Prices of antiretroviral (ARV) drugs in lower income countries have decreased substantially over the past two decades, helping to facilitate greatly expanded access to antiretroviral therapy (ART). However, ART coverage in many parts of the world remains low. We investigate the extent of epidemiological benefits that might be expected if ARV drug prices decline further. Design: A modeling study using data from seven countries in West and Central Africa (Cameroon, Democratic Republic of the Congo, Côte d'Ivoire, Niger, Nigeria, Senegal, and Togo). Methods: We investigated how the timing of ARV cost reductions could affect the impact and compared three different possible investment strategies: reinvesting in ART, reinvesting in the HIV response according to historical allocations, and reinvesting with the aim of minimizing HIV incidence and mortality. Results: If ARV drug prices fell by 37% relative to 2018 levels (i.e. following continued trend declines), we calculate ART unit costs could decrease by ∼20% (holding other cost components constant). If this could be achieved by 2020 and the savings were reinvested into ART, we estimate that an additional 8% of HIV infections and 11% of HIV-related deaths could be averted over 2020–2030 across the seven countries. Slightly greater gains could be attained if funds were reinvested in ART in combination with primary prevention. Delays in the year of introduction of ARV price reductions would reduce the impact by about 1% per year. Conclusion: ARV price reductions could free up funds that – if strategically invested – would help countries move closer toward the elimination of HIV. Abstract : Supplemental Digital Content is available in the text